History of abuse and adolescent hostile-helpless attachment: The mediating role of mother-adolescent punitive interactions. (June 2023) - Wells, Jasmine; Knoll, Monja Angelika; Lyons-Ruth, Karlen; Obsuth, Ingrid
Abstract: Background: Hostile-Helpless (HH) state of mind is a form of disorganised attachment that is strongly associated with prior experiences of abuse. However, how abuse experiences contribute toward HH states of mind in late adolescence is unknown. Punitive control in adolescent-mother dyads has been implicated in the development of HH states of mind and adolescent sex/gender may influence how punitive interactions contribute to HH mind states. Objective: The present study aimed to explore how adolescent sex/gender and punitive control within adolescent-mother dyads are related to the links between HH states of mind and childhood abuse. Participants and setting: A sample of 109 low-moderate income late adolescents (aged 18–23 years, 65 females, 44 males) and their mothers were assessed in a conflict-resolution paradigm. Methods: Recordings of the interactions were coded using the Goal-Corrected Partnership in Adolescence Coding System for different aspects of attachment-based interactions including punitive control. Late-adolescent HH states of mind features were coded from Adult Attachment Interviews (AAI) and experiences of abuse were coded from adolescent self-reports and the AAI. Results: Moderated mediation analysis revealed a significant indirect pathway from abuse to HH states of mind through punitive control in late adolescent females (B = 0.06, SEBoot = 0.04, 95 % CIBoot 0.01, 0.15), but not males (B = −0.02, SEBoot = 0.02, 95 % CIBoot − 0.07, 0.02). Conclusions: The results indicate that there are sex/gender-specific pathways to developing HH states of mind. Hostile behavior within mother-daughter dyads therefore may play an important role in linking abuse experiences and contradictory attachment representations in late adolescent females.